Capacidade de inovação organizacional: uma análise aplicada à indústria de transformação paulista - Facó, Júlio Francisco Blumetti (2009)
The main objective of this research was to explore relationship between organizational innovativeness and organizational slack in manufacturing companies at São Paulo State/Brazil regarding several industries. This research also tested, in a value chain basis, a model concerning cooperation as organizational innovativeness driver, as well as verified organizational innovativeness influence on firm performance. This research used two methodological approaches: quantitative and qualitative ones complementing each other. Concerning the quantitative approach, the Sondagem das Necessidades de Inovação na Indústria Paulista (SNIIP) research was used. The SNIIP was made by Federação das Indústrias do Estado de São Paulo (FIESP). This database has 229 companies from 24 different manufacturing industries at São Paulo State. The research tool used in this quantitative study was the statistical technique of multiple regressions, Concerning the qualitative approach, a sample of 9 medium and large companies from different manufacturing industries was used. The research tool used in this qualitative study was case study in order to complement and deepen the analysis of the previous quantitative study. The main results of this study are that organizational slack positively influences organizational innovativeness; Cooperation, can be viewed as a driver and positively influences organizational innovativeness; and, organizational innovativeness, as well, positively influences firm performance.